Personal income tax (PIT) and economic growth in Nigeria: A Vector Autoregression (VAR) analysis - Akeem Adekunle Adeyemi; Ebipanipre Gabriel Mieseigha (Trends Economics and Management, 2019)
Purpose of the article: Quite a number of studies have shown that tax revenues significantly affect the economic growth in both developed and developing countries; however, there is scanty empirical evidence as regards whether personal income tax (a major component of tax revenue) affects economic growth in Nigeria. Methodology/methods: The ex-post facto research design was adopted and the theoretical framework was anchored on Laffer Curve Theory (LCT). Yearly time series data of personal income tax and the gross domestic product (GDP) were obtained from the Federal Inland Revenue Service (FIRS) and the Central Bank of Nigeria (CBN) statistical bulletins during theperiod 1987-2017. The data obtained was analysed using the Vector Autoregression (VAR) model via STATA 13.0. Scientific aim: This paper investigated the effect of personal income tax (PIT) on economic growth in Nigeria. Findings: The findings of the study revealed that personal income tax has significantly contributed to the level of economic growth in Nigeria, though negatively. Contributions: Based on the findings of the study, it was recommended that the regulatory framework of taxation in the country should put in place a more effective tax revenue generation system that can enhance better administration of personal income tax. The measure should emphasise and address the accountability of personal income tax. In addition, a well-equipped database on personal income tax or taxpayers should be established by the governments with the aim of identifying all possible sources of income of taxpayers.
Keywords: M4; M01; 650; taxation; personal income tax; economic growth; government budget; Nigeria